Defining household exposure to the food environment: A comparison of measures based on residential area and activity space. - Simon Vonthron; Hélène Charreire; Marlène Perignon; Pascaline Rollet; Daisy Recchia; Caroline Mejean; Christophe-Toussaint Soulard; Coline Perrin; Surfood-Foodscapes study group (PLoS ONE)
The food environment's impact on food behaviors is widely recognized, yet there is no consensus on how to measure individual exposure, potentially leading to inconsistent results. This study aimed to assess how the relationship between food environment exposure and household characteristics differs based on whether exposure is measured solely via buffers around the home or extended to cover activity spaces. Data from the Mont'Panier cross-sectional study, comprising 699 households in Montpellier city-region, France, were analyzed. We used multivariate multinomial regression models and multiple logistic regression models to explore the associations between household characteristics and five indicators of households' food environment exposure: number of food stores, number of restaurants, diversity of food stores, relative density of stores selling fruits and vegetables, and relative density of fast-food restaurants. Exposure was measured using two methods: (i) 500m network-buffers around household's home; and (ii) activity spaces delimited using the daily path area method. Our findings confirm that social disparities in food environment exposure can vary based on the defined exposure area. Variables such as 'employment status' and 'education', not associated with indicators of food environment exposure around the home, show associations in the activity space. Conversely, 'age' and 'car ownership' are associated with various indicators of food environment exposure around the home but not in the activity space. Additionally, our analysis reveals that the abundance and diversity of food outlets tend to decrease as household's distance from the city center increases. Combining measures of food exposure (residential area, activity space) presents a promising approach to understanding food environment dynamics. Future research should investigate whether and how the choice of exposure measures affects food behaviors relative to households' socioeconomic characteristics. Lastly, we propose two avenues for reflection concerning public policy.